Protective effects of P2X7R antagonist in sepsis‐induced acute lung injury in mice via regulation of circ_0001679 and circ_0001212 and downstream Pln, Cdh2, and Nprl3 expression. (30th September 2020) - Zou, Zijun; Wang, Qin; Zhou, Minggen; Li, Weichao; Zheng, Yikai; Li, Fanyi; Zheng, Shengcai; He, Zhijie
Abstract: Background: Sepsis induces pulmonary P2X7 receptor (P2X7 R) expression and P2X7 R‐knockout reduced lung inflammation in mice. The present study investigated the expression of circular RNA (circRNA) and mRNA in sepsis‐induced acute lung injury (ALI) treated with a P2X7 R antagonist. Methods: Sepsis was induced by tracheal administration of lipopolysaccharide (LPS), and the mice were then divided into two groups: without [sepsis + dimethyl sulfoxide (DMSO)] or with P2X7 R antagonist treatment (sepsis + P2X7 A). Sham mice were administrated sterile normal saline. Serum levels of interleukin (IL)‐1β and tumor necrosis factor (TNF)‐α, pathological changes, cell apoptosis and P2X7 R expression in lung were assessed, followed by RNA sequencing (RNA‐seq) and bioinformatics analyses. A quantitative reverse transcriptase‐polymerase chain reaction (RT‐qPCR) was used to validate circRNAs and mRNAs. Results: Compared to the sham group, LPS‐induced sepsis produced obvious pathological changes in lung tissue, as well as increased apoptotic lung cells, serum TNF‐α and IL‐1β levels, and P2X7 R expression; P2X7 R antagonism significantly ameliorated these changes. RNA‐seq identified many dysregulated circRNAs and mRNAs during sepsis, whereas this changed with P2X7 R antagonism. RT‐qPCR confirmed that Mus musculus (mmu)_circ_0001679, mmu_circ_0001212, phospholamban (Pln), cadherin‐2 (Cdh2) and nitrogen permease regulator 3‐like (Nprl3) expression were significantly increased in the sepsis + DMSO group compared to that in the sham group but were decreased in the sepsis + P2X7 A group compared to that in the sepsis + DMSO group. The circRNA–microRNA–mRNA coexpression network indicated that mmu_circ_0001679 may regulate Nprl3 and that mmu_circ_0001212 may similarly regulate Pln, Cdh2 and Nprl3 as a competing endogenous RNA. Conclusions: P2X7 R antagonism attenuates sepsis‐induced ALI by inhibiting dysregulated expression of circRNA (circ_0001679, circ_0001212) and mRNA (Pln, Cdh2 and Nprl3). Abstract : Validation of the expression and circular structure of five differentially expressed circular RNAs (circRNAs). A reverse transcriptase‐quantitative polymerase chain reaction showed that circRNAs presented consistent expression patterns among the three groups, which were consistent with the sequencing results, except Mus musculus (mmu)_circ_0000372. The complementary DNA of five circRNAs was amplified by both divergent and convergent primers, although genomic DNA was amplified only by convergent primers. Spliced‐joint position was validated using Sanger sequencing (* p  < 0.05; ** p  < 0.01).